SIFAT FISIKOKIMIA TEH TALUA INSTAN METODE SPRAY DRYING DENGAN PERLAKUAN JENIS TELUR YANG BERBEDA - devi kumala sari; Tety Desrita Handayani; Nela Eska Putri Putri (Jurnal Sains dan Teknologi Pangan, 2023)
ABSTRACT Tea talua is a traditional Minangkabau drink made from tea mixed with egg yolks and beaten with sugar and some other additives. Currently there are no instant talua tea drinks available. Instant drinks are usually in powder form served in airtight packages. Powdered drinks are prepared by quick drying with the addition of coating agents. This study aims to determine the effect of different types of eggs on the physicochemical quality of instant egg tea produced. This research method used a completely randomized design (CRD) which consisted of 3 types of treatment and 3 repetitions. This study used a completely randomized design (CRD) with 3 treatments and 3 replications. The treatment given was the difference between egg yolks as raw material for talua tea, including: R = chicken eggs, B = duck eggs, and K = native chicken eggs, so that 9 treatment units were obtained. Data were analyzed using Analysis of Variance (ANOVA) and Duncan's Multiple Range Test (DMRT) at 95% confidence level. The use of different types of eggs did not differ significantly in the proximate test, namely moisture content (2.17+0.40 - 2.41+0.26%), ash content (1.02 + 0.02 - 1.05 + 0.06%), fat content (6.43 + 3.86 - 7.98 +2.10%), protein content (7.74+1.34 - 8.3+0.53%), carbohydrate content (80.48+2.78 - 82.39 +4.47 %)  and the yield (6.70 +0.55 - 8.61 +2.15 % )of instant talua tea produced Keywords: instan drink, egg, tea, teh talua.